Strategy to Create Indonesia Free Corruption in 2020 - Jawade Hafidz (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
A prosperous nation is a nation that has a system of transparency and leadership trustworthy, honest, and intelligent sermons. Four things that become the basic law of nationality and the embodiment of leadership strength of law are evident. Corruption became a thorn, state institution run lameness healthy. The law became a thorn plucker should be included affirmation indiscriminately; there is no collusion and nepotism against any citizen there. Indonesia will be developed by 2020 on condition free of corruption. This fact would have been possible if it has a clean leader, law walk uprightly and fair, community synergies with trust laws and leaders. Leaders from the President to the price level as like; “civil organization” be absolutely necessary for the law and society. Free of strategy from corruption in 2020 is not likely to happen if the three pillars of the leaders, law and society work together with the unanimous support towards Indonesia clean of corruption. Not just jargon, but the real work.Keywords: leadership, corruption, strategy